MICRO (MATSERALNY) COMPOSITION OF ORGANIC MATTER HUMUS YARUDEYSKIY PARAMETRIC WELLS 38 - Belyaeva, G.L. (Perm Federal Research Centre Journal, 2016)
The detailed study of the sedimentary section (Jurassic and Triassic sediments) Yarudeyskiy parametric well 38 slaughter 5 010 m drilled on the territory of Nadym district of Yamal-Nenets Autonomous District. Investigated MICRO (matseralny) the composition of humic organic matter (OM) of core samples from the interval 3 611.5-4 146 m. It is established matseralnogo diversity of humic OM and assumed the conclusion that the dominant depositional kotuhtinskoe (Pliensbachian- Toarcian) and tyyavinskoe (ladinsko-Carnic) time was facies silnoobvodnennyh stagnant forest swamps, which are periodically dried up, moving in slabouvlazhnennye.